2008
DOI: 10.3208/sandf.48.41
|View full text |Cite
|
Sign up to set email alerts
|

Various Viscosity Types of Geomaterials in Shear and Their Mathematical Expression

Abstract: The viscous properties, or loading-rate eŠects on the stress-strain behaviour, of unbound and bound soils, in particular unbound granular materials, are summarised. The viscous properties were evaluated by stepwise changing the strain rate, ·e, and performing sustained loading during otherwise monotonic loading (ML) at a constant ·e and also by performing ML tests at diŠerent constant values of ·e. Four basic viscosity types, Isotach, Combined, TESRA (or Viscous Evanescent) and Positive & Negative (P & N), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 28 publications
2
67
0
Order By: Relevance
“…Though some authors provide numerical roundness values (e.g. Rouse et al, 2014, Yoshimoto et al, 2012Tatsuoka et al, 2008), in geotechnical research authors more commonly describe roundness qualitatively.…”
Section: Measurement Of Shape Descriptorsmentioning
confidence: 99%
“…Though some authors provide numerical roundness values (e.g. Rouse et al, 2014, Yoshimoto et al, 2012Tatsuoka et al, 2008), in geotechnical research authors more commonly describe roundness qualitatively.…”
Section: Measurement Of Shape Descriptorsmentioning
confidence: 99%
“…So, the strength during ML at constant ·e decreases with an increase in ·e. Enomoto et al (2007), and Tatsuoka et al (2008) reported that the four viscosity types described above can be classiˆed by the viscosity type parameter, u, deˆned as:…”
Section: Introductionmentioning
confidence: 99%
“…The viscous property is a function of instantaneous irreversible (or visco-plastic) strain rate ( ·e ir or ·e vp ) and other relevant parameters, not by time Tatsuoka et al, 2002Tatsuoka et al, , 2003Tatsuoka et al, , 2008Tatsuoka, 2004. Geomaterials in theˆeld have been aged at early or late stages of diagenetic process on the geological or engineering time scale, or in between.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the time-eŠects on the stress-strain behaviour of geomaterial should be understood correctly and properly. Even if the in‰uence of pore water pressure changes is not involved, the following two types of time eŠects should be taken into account (e.g., Di Benedetto et al, 2005;Tatsuoka et al, 2008): the ageing eŠect, which can be deˆned as``changes with time in the intrinsic stress-strain properties due to time-dependent changes in interface and/or internal particle properties caused by a physico-chemical process'' and the``viscous or loading rate eŠect'', which can be attributed primarily to the``viscous deformation and sliding at inter-particle contact points and its eŠects on the structural stability of a given soil mass''. The viscous or loading rate eŠect is the topic of this paper.…”
Section: Introductionmentioning
confidence: 99%